Conceptual foundations of pharmacoeconomic analysis of prevention technologies of chronic viral infections - S. O. Soloviov; I. V. Dziublyk; V. V. Trokhymchuk (The State Expert Center of the Ministry of Health of Ukraine, 2019)
The introduction of various technologies for the prevention of chronic viral infections into practice requires well-founded evidence of their effectiveness, which can be obtained using pharmacoeconomic methods and models that determine not only the effectiveness and feasibility of introducing preventive technologies, but also the socio-economic associated consequences. In this context, the development of a unified model for the pharmacoeconomic evaluation of medical technologies at all stages of the prevention of chronic viral infections is key to implementing optimal strategies for combating them for both individual groups and the entire population, developing recommendations for the rational use of diagnostic tests and viral vaccines, and determining the optimal level of pharmaceutical care for patients. The aim of the work - development of a conceptual model of pharmacoeconomic analysis of technologies for the prevention of chronic viral infections. Pharmacoeconomic evaluation of technologies for the prevention of chronic viral infections is possible on the basis of an analytical platform that determines the relationship between the target population to be prevented, and the effectiveness of intermediate and final results. The pharmacoeconomic analysis of technologies for the prevention of socially significant chronic viral infections was proposed to be carried out according to the developed algorithm. Implementation of the proposed algorithm for pharmacoeconomic analysis of various technologies for the prevention of chronic viral infections was based on developed unified model of the spread of viral infection in the population, where individuals can be assigned to different clinical and epidemiological classes. This model was a combination of epidemiological and clinical prognostic approaches and can be used to predict and conduct pharmacoeconomic assessment of viral infection prevention technologies with a general decrease in the number of people in a particular epidemiological class when applying medical technology for a certain period of time. The presented concept allows to formulate the principles of pharmacoeconomic evaluation of technologies for the prevention of chronic viral infections. It was advisable to use the concept of quality of life in assessing the usefulness of the technologies under study, which allows to formalize the cost-utility coefficient, minimization of which determines pharmacoeconomic reasonable strategies for the prevention of chronic viral infections. The developed concept is promising, and information technologies based on it can become a reliable source of information to support decision-making by health experts in the pharmacoeconomic evaluation of technologies for the prevention of chronic viral infections.